2022
DOI: 10.33003/fjs-2021-0504-683
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Implications of Heavy Metals in Drinking Water Sources of Loko and Mararraba in Nasarawa State, Nigeria

Abstract: Metals are substances with high electrical conductivity, malleability, and luster, which voluntarily lose their electrons to form cations. This study aimed at assessing the Toxic implications of Heavy Metals in Drinking Water Sources of Loko and Mararraba in Nasarawa using Micro Plasma Atomic Emission Spectroscopy (MP-AES). The results showed that, seven heavy metals along with their respective concentrations for both Loko and Mararraba in mg/L (Zn (0.19 and 0.23), Cd (0.00 and 0.00), Fe (0.05 and 0.04), Cu (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…According to a 2010 assessment by Darko et al, as reported by Rilwan et al in 2022 [4,5] the people of Nasarawa only use untreated groundwater (from wells and boreholes) and surface water sources. This is due to the limited number of pipe-borne water sources that are available and the fact that they are frequently inoperable.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to a 2010 assessment by Darko et al, as reported by Rilwan et al in 2022 [4,5] the people of Nasarawa only use untreated groundwater (from wells and boreholes) and surface water sources. This is due to the limited number of pipe-borne water sources that are available and the fact that they are frequently inoperable.…”
Section: Introductionmentioning
confidence: 99%
“…A naturally occurring radioactive inert gas with a half-life of 3.82 days, Radon-222 is soluble in water and belongs to the uranium decay series. The majority of the radiation from all-natural sources comes from it [5] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations